Schaum's Physics Supplementary Problem 15-14: Bernoulli's Principle - Mitra-Kirtley, Sudipa (McGraw-Hill's AccessEngineering., 2013)
This video demonstrates the solution to a problem that uses the balance of forces involving different buoyant forces.